The Validity of the Binding Sale and Purchase Agreement (PPJB) in the presence of a Notary related to the incomplete basis of land rights - Febrihadi Suparidho; Yuni Ristanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Sale and Purchase Binding Agreement (PPJB) is one of the legal instruments commonly used in the practice of land purchase and sale transactions in Indonesia. PPJB is generally made when the parties have reached an agreement on the object and price, but have not been able to pour it into the Deed of Sale and Purchase (AJB) due to various administrative constraints, including incomplete land rights base. On the other hand, Article 1320 of the Civil Code requires the existence of a certain thing and halal cause as an objective condition for the validity of the agreement. This condition raises juridical problems: whether the PPJB made before a notary can still be declared valid and binding if the basis of land rights is not perfect, and how the notary is accountable in making the deed. This research is a normative legal research with a legislative approach, a conceptual approach, and a limited case approach. The results of the study show that PPJB with incomplete rights can basically still be declared valid as long as it meets the legal requirements of the agreement, especially regarding the agreement of the parties and the clarity of the agreed object, but the agreement only gives birth to the rights and obligations of the obligate and does not necessarily transfer the rights to the land. Notaries are obliged to conduct a reasonableness examination on the grounds of rights submitted by the parties, provide adequate explanations of legal risks, and refuse to make deeds if they are clearly contrary to laws and regulations. However, notaries are not burdened with the obligation to ensure the material correctness of land ownership, so that the notary's civil liability can only be requested if it is proven to be negligent or acts beyond the limits of his authority.